2009
DOI: 10.1063/1.3184573
|View full text |Cite
|
Sign up to set email alerts
|

Employing two distinct photonic crystal resonances to improve fluorescence enhancement

Abstract: Surface-bound fluorescence assays such as microarrays have emerged as a prominent technology in current life sciences research and are currently performed on optically passive substrates such as glass microscope slides. We present an alternative approach using photonic crystal substrates exhibiting resonant reflections. In this work, we design and fabricate a photonic crystal with a TM-polarized resonance at the cyanine-5 excitation wavelength and a TE-polarized resonance spectrally overlapping this fluorophor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
42
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 9 publications
2
42
0
Order By: Relevance
“…Fortunately, Cunningham et al realized remarkable enhancement of fluorescence (ca. 108-fold) from quantum dots on the two-dimensional PC slabs with dual band gaps due to a combination of highintensity near fields and strong coherent scattering effects of guided resonance [20,21]. Enlightened by the work, we develop a facile approach on self-assembled heterostructure PCs with dual stopbands to enhance the fluorescent signal.…”
Section: Introductionmentioning
confidence: 96%
“…Fortunately, Cunningham et al realized remarkable enhancement of fluorescence (ca. 108-fold) from quantum dots on the two-dimensional PC slabs with dual band gaps due to a combination of highintensity near fields and strong coherent scattering effects of guided resonance [20,21]. Enlightened by the work, we develop a facile approach on self-assembled heterostructure PCs with dual stopbands to enhance the fluorescent signal.…”
Section: Introductionmentioning
confidence: 96%
“…In previous work, a confocal laser scanner, incorporating a focused laser beam, was used to good effect for PCEF [5,15]. However, due to the angle selectivity of the PCEF surface, only a portion of the excitation energy can be coupled into the resonance mode and contribute to enhanced fluorescence emission.…”
Section: Chapter 1: Introductionmentioning
confidence: 99%
“…While the effects of PC enhanced excitation and enhanced extraction can be combined with multiplicative effects [5,7,8], this work is primarily concerned with optimization of enhanced excitation through the interaction of the PC resonant mode characteristics and the degree of collimation of the illumination that is provided to the PC.…”
Section: Chapter 1: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous work, we have shown that an optimal design for PC enhanced fluorescence utilizes transverse magnetic (TM) polarized light (polarization perpendicular to grating direction) for normal excitation and transverse-electric (TE) polarized light (polarization parallel to grating direction) for extraction of the emitted fluorescence signal. 8 Therefore, the PC resonance was designed to be at normal-incidence excitation (h ¼ 0 ) for TM polarized light from a k ¼ 632.8 nm, He-Ne laser for fluorescence excitation. The geometry of the structure and the indices of the surrounding dielectric media determine the resonance wavelength of the PC.…”
mentioning
confidence: 99%